THE INFLUENCE OF WORK MOTIVATION ON EMPLOYEE PERFORMANCE WITH PRESENTEEISM AS AN INTERVENING VARIABLE AT THE BPJS OFFICE, TANJUNG MORAWA BRANCH - Hanif Nasution, Haikal; Isa Indrawan, Muhammad (Penerbit Lafadz Jaya, 2023)
This research aims to see the influence of work motivation on employee performance with presenteeism as an intervening variable. This research uses a quantitative type of research, this research was conducted at the BPJS Tanjung Morawa branch office, the research population was 70 employees and the sample for this research was the entire population. The sampling technique used was a saturated sample. The data collection used was a questionnaire. The research model used is expert analysis and this research uses SPSS version 25. The results of this research are as follows: Work Motivation has a positive and significant effect on Presenteeism. Work Motivation has a positive and significant effect on Employee Performance. Presenteeism has a positive and insignificant effect on employee performance. Indirect Influence of Work Motivation on Employee Performance through Presenteeism.